Pharmacological polyamine catabolism upregulation with methionine salvage pathway inhibition as an effective prostate cancer therapy - Hayley C. Affronti (Nature Portfolio, 2020)
Prostate cancer cells depend on MTAP, the rate-limiting enzyme involved in the methionine salvage pathway, to cope with increased polyamine biosynthesis. Here, the authors show that inducing upregulation of polyamine biosynthesis and targeting MTAP synergize to increase apoptosis in prostate cancer cells.